Infusion of the Branched Chain Amino Acids in Postoperative Patients: Anticatabolic Properties - Freund, Herbert (1979)
Postinjury metabolism is characterized by breakdown of muscle protein as substrate for energy production and gluconeogenesis and by the resultant loss of lean body mass and weight loss. The branched chain amino acids (BCAAs) which are principally oxidized by the skeletal muscle have been implicated in recent in vitro and in vivo studies as having special anticatabolic and regulating effects in skeletal muscle. We studied the anticatabolic effects of the BCAAs in 35 patients undergoing operative injury of moderate severity. In a prospective randomized and blinded manner patients were infused for five days starting immediately after surgery with either 5% dextrose or 5% dextrose with an amino acid solution containing 22, 35 or 100% BCAAs. All patients survived and there were no major postoperative complications. Mean hospital stay was 17 days for patients receiving amino acids and 19 days for patients receiving 5% dextrose only (p = ns). All three groups receiving amino acid solutions were in nitrogen equilibrium or in a slight positive nitrogen balance, while the group receiving 5% dextrose only was in a mean negative nitrogen balance of 6.6 ± 0.6 gN/day. The differences between the three groups receiving amino acids were slight and not significant. Weight loss was 2 ± 0.7 kg in the 5% dextrose group, 1 ± 0.7 kg in the 22% BCAAs group, 0.5 ± 0.5 kg in the 35% BCAAs group and the 100% BCAAs group gained 0.4 ± 1.8 kg. Blood chemistries in the different groups and during the study period remained within normal limits except for ammonia levels rising significantly in the 5% dextrose group and SGOT levels rising in the 22% and 35% BCAA groups. With mild variations the plasma amino acid patterns in all groups were similar to the normal pattern, even in the 100% BCAAs group receiving an unbalanced amino acid solution, suggesting the complete cessation of amino acid efflux from muscle, the muscle depending solely on the exogenous supply of BCAAs to satisfy its metabolic requirements. The results suggest that early nutritional suppport in the postoperative period will result in nitrogen equilibrium and that the infusion of the three BCAAs only in the postoperative state is as effective in preventing muscle catabolism as other more balanced amino acid solutions. In the postinjury state balanced amino acid solutions rich in BCAA may prove beneficial.